A Reflection on Lithium‐Ion Batteries from a Lithium‐Resource Perspective. Issue 10 (25th June 2021) - Zu, Chenxi; Ren, Yu; Guo, Fuliang; Yu, Huigen; Li, Hong
Abstract : The increasing consumption of fossil fuels is driving environmental concern, requiring lithium‐ion batteries (LIBs) to support a shift of energy supply to clean energies. Specifically, it is imperative that the market of electric vehicles (EVs) is decarbonized, which demands a consistent supply of LIBs and lithium. For sustainable use of lithium resources, it is time to look back at the cell composition of LIBs and combinations of various cathode and anode chemistries that enable high energy density with high lithium‐use efficiency. Herein, the theoretical and practical gravimetric energy density of cells of major electrode combinations is calculated and lithium use in each cell to achieve per kilowatt hour energy is analyzed. Then effective strategies that improve the lithium‐use efficiency are suggested, including enhancing the Coulombic efficiency, extending the cycle life, using retired power battery in the grid storage, and recycling. Finally, lithium consumption in the emerging market of EVs and grid storage is predicted and it is concluded that recycling is imperative to relieve lithium anxiety. Abstract : How to design a proper cell chemistry that possesses high energy density and lithium‐use efficiency is critical from a lithium‐resource perspective. Herein, the cell composition of LIBs and combinations of various cathode and anode chemistries that enable high energy density with high lithium‐use efficiency are looked at and a perspective on this question is provided.